A Qualitative Study of Information Needs about Human papillomavirus (HPV) Among Elementary School Students - Syahrani, Dilla; Mutiar, Astri; Marfuah, Dewi; Purnama, Heni (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This research aims to to identify the information requirements of elementary school children toward human papillomavirus (HPV). Methods: The researcher employed a qualitative method utilizing the focus group discussion technique to gather data on several predetermined topics. A total of 20 female students who met the criteria were divided into several groups, and the discussions were recorded and documented. Result: Most of elementary school children have no background knowledge of HPV. Many of them have limited understanding of sexual health education. Although children aged 9-14 have received the HPV vaccine, most of them do not know about HPV. Further information is needed regarding the definition of HPV, the virus transmission process, potential symptoms, diseases caused by the virus, and complications arising from inadequate attention to prevention. Conclution: Providing comprehensive and child-friendly information about the HPV virus is essential to enhance the knowledge of elementary school students. It also contributes to increasing the acceptance of the HPV vaccine and maximizing preventive measures.